PENERAPAN DAN PENYAJIAN LAPORAN KEUANGAN SESUAI STANDAR AKUNTANSI KEUANGAN ENTITAS MIKRO, KECIL, DAN MENENGAH - Novita Mardiani; Hadi Sucipto (STIE PGRI Dewantara Jombang, 2022)
This study aims to determine the application and presentation of financial statements in accordance with micro, small and medium entity financial accounting standards at UD Tiga Putra. This research is a qualitative descriptive study. Sources of data in this study used primary data types obtained through interviews, documentation, and observation. From the results of the study it is known that: 1) UD Tiga Putra has not fully implemented correctly due to limited human resources, 2) UD Tiga Putra acknowledges the recognition and measurement of several accounts in the statement of financial position such as inventory accounts, payables, accounts receivable, and capital; 3) UD Tiga also recognizes the recognition and measurement of income accounts in the income statement that have not been realized in the form of financial statements according to SAK. From the results of this study, it is suggested to business owners to increase the capacity of their employees, especially those in charge of recording transactions to presenting financial reports. Some things that can be done include participating in training, especially regarding the presentation of financial reports or collaborating with universities to be willing to provide assistance at UD Tiga Putra.